PENANGGULANGAN KERUSAKAN LINGKUNGAN AKIBAT ABRASI PANTAI DI KABUPATEN BENGKALIS - Rati Jusliyanti (JURNAL SENPLING MULTIDISIPLIN INDONESIA, 2024)
One of the damage to the coastline can be triggered by the disruption of the natural balance in the coastal area. Overcoming coastal abrasion requires comprehensive, sustainable and involving all parties. Various efforts have been made by the Bengkalis Regency Government. This qualitative descriptive research was conducted in September 2022 using field survey methods and literature studies. From the results of the discussion, it can be concluded as follows: 1. Efforts to overcome abrasion through the construction of coastal protection, only 23.7% of the beaches affected by abrasion have been realized and have not run optimally and 2. Efforts to plant mangroves on peat soil have not been successful and mangrove planting on clay Clay has not found a planting technique that can prevent mangrove seedlings from being carried away by currents or sea waves.